Analisis Kesesuaian Lokasi Pengembangan Ruang Terbuka Hijau Publik Di Kecamatan Palu Timur Dan Palu Barat - ACHSAN, ANDI CHAIRUL (Jurnal Arsitektur Lansekap; Vol.1, No.2, Oktober 2015DO - 10.24843/JAL.2015.v01.i02.p04, 2015)
ABSTRA CT Suitability Analysis o f The Location o f The Development Public Green Open Space i n The Sub District Palu Timur a nd Palu Barat The existence of green open spaces, especially for public green open spaces in the region of Palu City still showing lack of suitability with public aspect, therefore, to optimize the function of public space as a place for comfortable activities required the suitability analysis of the location to identify and determine prioritize the location of the development of public green open space based on aspects of the fulfillment of public functions. The purpose of this study was to identify and map the aspects that influence as well as analyze and determine the suitability of the location of the development of public green open space in the sub district of Palu Timur and Palu Barat. The results  showed the suitability class of the location of development public green open space was divided into four class not suitable, enough suitable, suitable and very suitable.Based on the determination of suitability of location can be determined the priority of the location of the development of public green open space in the subdistrict Palu Timur and Palu Barat was located on an area with the suitability level very suitable with an area for subdistrict Palu Timur 885.576,32 m 2 and Palu Barat 661.986,41 m 2 .   Keywords: suitability, location, green open space